The Dynamics of the Death Penalty as a Deterrent or Preventive Tool - Saleh, Muhammad; Calvin, Calvin (Universitas Islam Negeri Sumatera Utara, 2023)
Death penalty is the most extreme punishment imposed by a country's legal system against perpetrators of certain crimes. In the context of the dynamics of criminal law, there are arguments stating that the death penalty has a role as a deterrence or prevention tool against crime. This paper explores the dynamics of the death penalty as a deterrence or preventive tool in the context of the legal system, with a focus on controversy, effectiveness, and implications in law enforcement. Various opinions and studies support and oppose the effectiveness of death penalty as a deterrence tool. Some argue that the death penalty can reduce the level of crime due to the potential for serious consequences, thus preventing others from committing similar crimes. However, other opinions indicate that there is no strong empirical evidence to support the claim that the death penalty is truly effective in reducing crime rates. Some studies even show that other factors such as prevention policies, rehabilitation, and improvement of social conditions are more influential in reducing crime than the threat of the death penalty. The controversy surrounding the death penalty also involves ethical considerations, human rights, and principles of justice. The death penalty is often considered a violation of human rights, especially the right to life which is considered an inviolable human right. In addition, the risk of error in law enforcement is also a major concern, where systematic errors can result in the execution of innocent people. The implication of death penalty dynamics as a deterrence tool also involves aspects of public policy and social change. Some countries have abolished death penalty as a step towards more humane justice and fairer legal system. Meanwhile, other countries continue to maintain the death penalty as part of their legal system, although controversies and challenges continue to arise in the application and justification of the punishment. In conclusion, the dynamics of the death penalty as a deterrence tool is still a complex and controversial topic in the study of criminal law and policy. Although some opinions support its effectiveness in deterring crime, there are also many arguments and evidence to the contrary. Therefore, there is a need for more in-depth studies and strong empirical evidence to better understand the role and impact of death penalty in society and legal system.